INCLUSIVE VILLAGE, REVIEW OF VILLAGE GOVERNMENT CAPACITY IN EMPOWERING DISABILITIES(STUDY IN SUMBERRAHAYU VILLAGE, KAPANEWON MOYUDAN, SLEMAN REGENCY, SPECIAL REGION OF YOGYAKARTA) - Adji Suradji Muhammad; Cici Sriyanti; Eka Suswaini (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This study aims to find out how the capacity of the Sumberrahayu Village Government is in relation to persons with disabilities in the Inclusive Village Program. Through a qualitative descriptive approach with supporting data based on interviews, observation, and documentation, the data is then collected and validated before conclusions are drawn. Based on the various data obtained, it is known that the Sumberrrahayu Kapanewon Moyudan Village Government has the capacity to empower persons with disabilities. This capacity is demonstrated by the issuance of Village Regulation Number 01 of 2015 concerning the 2015–2020 Medium Term Development Plan, which includes persons with disabilities in the planning process. Apart from being involved in the process of preparing the RPJMDesa, the kelurahan government also provides funding for programs and activities that support the preservation of persons with disabilities, especially in the economic field, empowering rural communities with the aim of improving the management of social service activities in the education and health sectors. In addition, women's and children's groups are also empowered. This is done by the Kelurahan government with the aim that persons with disabilities, especially persons with severe disabilities, can increase their independence and participate actively in development and can enjoy the results of development equally.